Expert System Diagnosing Anxiety Disorder Using Based Naïve Bayes Method - Danvy Nadhira; Fristi Riandari (Institute of Computer Science (IOCS), 2021)
Psychological problems such as Anxiety Disorder have become a common problem in the world. Most sufferers of this disease are under 45 years old on average and usually this disorder often attacks the mentality of women. However, this disease is often considered trivial and not many sufferers realize it. Not to mention the handling of course requires quite a lot of money. Another thing is the lack of information about this disease, which causes the risk of sufferers of Anxiety Disorder to increase every year. To solve existing problems, it can be solved by using computer technology in the health sector that can diagnose a disease like an expert, namely an expert system application disease symptoms. The purpose of this study is as a first step to treat this disorder as quickly as possible. The application of the Naïve Bayes method plays a role in being able to provide diagnostic results because the Naïve Bayes method is considered capable of providing the largest clarification of the value of v based on the selected symptoms.